UJI DAYA HAMBAT EKSTRAK Cymbopogon citratus DAN Alpinia purpurata TERHADAP PERTUMBUHAN Shigella sonnei - Laili Fitri Yeni; Eko Sri Wahyuni; Junika Mandasari; Dinda Triana (Jurnal Biosilampari : Jurnal Biologi, 2022)
This study aimed to determine the phytochemical content and potency of the ethanol extract of lemongrass (Cymbopogon citratus) stem and red galangal rhizome (Alpinia purpurata) in inhibiting the growth of Shigella sonnei in vitro. Phytochemical testing of ethanol extract using Thin Layer Chromatography (TLC). Antibacterial test was carried out by applying the Kirby Baeur disk diffusion method with swab technique with a series treatment of extract concentrations of 6.25%, 12.5%, 25%, 50%, positive control (tetracycline 20%), and negative control (DMSO 10%) with 5 replicates. From the results of phytochemical tests, showed that secondary metabolites of flavonoids and terpenoids were found in red galangal extract. While the lemongrass extract showed positive results for alkaloids, flavonoids, terpenoids and phenolic compounds. The ethanol extract of lemongrass stem and galangal rhizome potential as an antibacterial with the highest inhibitory activity obtained at a concentration of 50% in both lemongrass and galangal extracts, respectively 8.4 mm and 7 mm. The results of the antibacterial test showed that red galangal extract and lemongrass extract had phytochemical contents that could inhibited the growth of S. sonnei.